Increased time between diagnosis and surgery in slipped capital femoral epiphysis results in increased radiographic deformity - Fedorak, G. T. (J Child Orthop, 2018)
PURPOSE: Previous work has examined the impact of delay of diagnosis in slipped capital femoral epiphysis (SCFE) but not the impact of delay in treatment after radiographic diagnosis. Due to requirements for long distance transportation from less developed regions for many of our patients, our hospital was able to study variation in time between diagnosis and surgery for SCFE, as related to slip severity. METHODS: This is a retrospective review of patients treated for SCFE between 2005 and 2014 at a tertiary care paediatric hospital. Demographics, time between diagnosis and surgery, radiographic deformity (Southwick angle), postoperative complications and need for further surgery were variables of interest. Statistical analysis included Pearson and Spearman rank correlations and chi-squared tests. RESULTS: The study sample included 147 hips (119 patients). Mean time between radiographic diagnosis and surgery was 20.9 days (sd 46, 0 to 321). The mean Southwick angle (SA) at the time of surgery was 31.9˚ (sd 19.6˚, 1° to 83˚). There was a significant relationship between increased delay and increased SA (0.34, p < 0.001). Increased SA was correlated with need for future significant surgery (0.27, p < 0.01). Patients from less-developed regions, with barriers to timely care, had moderate and severe deformity (SA) (p < 0.01), and required significant further surgery more often than SCFE patients from the local population (p < 0.01) CONCLUSION: The unique referral environment of our hospital provided an opportunity to examine traditional recommendations for treating SCFE promptly after radiographic diagnosis. Delay in treatment is correlated with increased radiographic deformity. LEVEL OF EVIDENCE: III